2016
DOI: 10.1089/scd.2016.0267
|View full text |Cite
|
Sign up to set email alerts
|

Daughters of the Enamel Organ: Development, Fate, and Function of the Stratum Intermedium, Stellate Reticulum, and Outer Enamel Epithelium

Abstract: The tooth enamel organ (EO) is a complex epithelial cell assembly involved in multiple aspects of tooth development, including amelogenesis. The present study focuses on the role of the nonameloblast layers of the EO, the stratum intermedium, the stellate reticulum, and the outer enamel epithelium (OEE). The secretory stage stratum intermedium was distinguished by p63-positive epithelial stem cell marks, highly specific alkaline phosphatase labeling, as well as multiple desmosomes and gap junctions. At the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
0
29
0
3
Order By: Relevance
“…Our previous studies had demonstrated the role of SI in enamel mineralization by the regulation of alkaline phosphatase activity in a mouse model ( Yoshizaki et al, 2014 , 2017 ). Some reports had earlier indicated that SI cells regulate ion transporters associated with ameloblast ( Liu H. et al, 2016 ). Solute carrier family member Slc4a4 (NBCe1) is complementarily expressed in ameloblasts and SI cells and has implicated functions in pH regulation during enamel mineralization ( Jalali et al, 2014 ), which is in agreement with our results ( Figure 2F ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies had demonstrated the role of SI in enamel mineralization by the regulation of alkaline phosphatase activity in a mouse model ( Yoshizaki et al, 2014 , 2017 ). Some reports had earlier indicated that SI cells regulate ion transporters associated with ameloblast ( Liu H. et al, 2016 ). Solute carrier family member Slc4a4 (NBCe1) is complementarily expressed in ameloblasts and SI cells and has implicated functions in pH regulation during enamel mineralization ( Jalali et al, 2014 ), which is in agreement with our results ( Figure 2F ).…”
Section: Discussionmentioning
confidence: 99%
“…During tooth development, cell proliferation markers such as Ki67 are strongly positive in IEE ( Chiba et al, 2019 ); however, OEE proliferates more actively than IEE during the formation of Hertwig’s epithelial root sheath ( Yokohama-Tamaki et al, 2006 ). Also, in pre-eruption molars, OEE seems to be potent for proliferation ( Liu H. et al, 2016 ). GO terms of the IEE/OEE cluster were enriched in cell mitosis ( Figure 2E ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratins function in epithelial cell shape and cell-cell adhesion 41,42 as cited by Pan, et al 43 KRT15 may help maintain the shape of dental epithelium progenitor cells and facilitate their migration within the developing tooth organ to contribute to the stellate intermedium and, eventually, their differentiation into ameloblasts and cells of the stellate reticulum. 44 Like KRT15 ( Figure 5E,M,U), Krt8 was expressed in the dental epithelium and tooth organ ( Figure 4U-X). Krt8 expression is repressed by the p63 transcription factor 45 and induced when ΔN-p63 is down-regulated.…”
Section: Cell Adhesion Shape and Apoptosis: Krt8 Krt15mentioning
confidence: 97%